Canadian content : culture and the quest for nationhood - Edwardson, Ryan, 1974- (Toronto ; Buffalo : University of Toronto Press, 2008)
Canadian Content looks at Canada as an ongoing postcolonial process of not one but a series of radically different nationhoods, each with its own valued but tentative set of cultural criteria for orchestrating and implementing a Canadian national experience.
Introduction: a guide to Canadianization -- Colony to nation: morality, modernity, and the nationalist use of culture -- Culturing Canada: the Massey Commission and the broadcasting, film, and arts triumvirate -- From institution to industry: mass media and state intervention, 1958-1966 -- Canadian content woes: cultural imbalance and undercurrents in the 1960s -- Creating the peaceable kingdom: a new nationalist Canadian identity -- Guaranteed culture: nationalism and the question of intervention -- Saving Canada: Pierre Trudeau and the mobilization of culture -- Littlest Hobos and Kings of Kensington: Canadian cultural melange in the 1970s -- From citizens to consumers: cultural industrialism and the commodification of Canadian content -- Canadianization in a time of globalization -- Conclusion: building Canada: culture and the quest ofr nationhood.
Includes bibliographical references (pages 325-343) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Canada -- Cultural policy -- History -- 20th century; Nationalism -- Canada -- History -- 20th century; Cultural industries -- Government policy -- Canada -- History -- 20th century; Cultural industries -- Canada -- History -- 20th century; Canada -- Politique culturelle -- Histoire -- 20e siècle.; Nationalisme -- Canada -- Histoire -- 20e siècle.; Industries culturelles -- Politique gouvernementale -- Canada -- Histoire -- 20e siècle.; Industries culturelles -- Canada -- Histoire -- 20e siècle.; HISTORY -- Canada -- General; HISTORY -- Canada -- Post-Confederation (1867- ); Cultural industries; Cultural policy; Nationalism; Canada; 1900-1999; History